(untitled) (Research, Society and Development, 2021)
This article aimed to describe the possible roles and perspectives to be assumed by bailiffs within societies 4.0. The study was based on an inductive and intuitive method, through documentary research focused on bills of law, local proposals and possible new attributions designed for the category. It was found that, in addition to the currently identified legislative proposals and local initiatives, the integration of bailiffs to new activities (such as judicial intelligence and the execution of new forms of patrimonial constriction) could represent the evolution of this category to a new useful level for the judiciary and society. Furthermore, the officers could go back to their past and reincorporate typical functions in the area of security and defense, thus meeting the needs arising from the determination of the CNJ to institute judicial police, raising these agents to a new category of public servants specialized in material execution of court orders.